Mitochondrial impairment and repair in the pathogenesis of systemic lupus erythematosus - Zhao, Like; Hu, Xianda; Xiao, Fei; Zhang, Xuan; Zhao, Lidan; Wang, Min (Frontiers in Immunology, 2022)
Nucleic acid autoantibodies, increase type I interferon (IFN-α) levels, and immune cell hyperactivation are hallmarks of systemic lupus erythematosus (SLE). Notably, immune cell activation requires high level of cellular energy that is predominately generated by the mitochondria. Mitochondrial reactive oxygen species (mROS), the byproduct of mitochondrial energy generation, serves as an essential mediator to control the activation and differentiation of cells and regulate the antigenicity of oxidized nucleoids within the mitochondria. Recently, clinical trials on normalization of mitochondrial redox imbalance by mROS scavengers and those investigating the recovery of defective mitophagy have provided novel insights into SLE prophylaxis and therapy. However, the precise mechanism underlying the role of oxidative stress-related mitochondrial molecules in skewing the cell fate at the molecular level remains unclear. This review outlines distinctive mitochondrial functions and pathways that are involved in immune responses and systematically delineates how mitochondrial dysfunction contributes to SLE pathogenesis. In addition, we provide a comprehensive overview of damaged mitochondrial function and impaired metabolic pathways in adaptive and innate immune cells and lupus-induced organ tissues. Furthermore, we summarize the potential of current mitochondria-targeting drugs for SLE treatment. Developing novel therapeutic approaches to regulate mitochondrial oxidative stress is a promising endeavor in the search for effective treatments for systemic autoimmune diseases, particularly SLE